Investigation of precipitate in an austenitic ODS steel containing a carbon-rich process control agent - Gräning, Tim; Rieth, Michael; Möslang, Anton; Kuzmin, Alexei; Anspoks, Andris; Timoshenko, Janis; Cintins, Arturs; Purans, Juris (Elsevier Ltd, 2018)
Austenitic oxide dispersion strengthened (ODS) steels are one of the candidates as a structural material for high-temperature applications in future power plants. To guarantee the necessary high production yield, the production process was improved in terms of reproducibility and scalability, by adding a process control agent (PCA) during the milling process. Due to this addition and the inherent change of the production process, the produced powder was thoroughly investigated using transmission electron microscopy and X-ray absorption spectroscopy methods to reveal the formation of chromium-rich carbides adjunct to titanium. Hence, less titanium was available to form the preferred complex nano-oxides the addition of carbon to the system influences the formation of precipitates severely in terms of their amount and size. The mechanical alloying process itself was unaffected by the addition of a PCA, and mixing and alloying of used elements still occurs.
This work has been carried out within the framework of the German Helmholtz Association and has received funding from the topic “Materials Research for the Future Energy Supply”. The work of M. Parish and Rainer Ziegler is gratefully acknowledged. Thanks are also due to the team of the chemical laboratory at the KIT for performing the chemical analysis. The help of the beamline staff at ELETTRA (project 20140052 ) synchrotron radiation facility is acknowledged. We acknowledge support by Deutsche Forschungsgemeinschaft and Open Access Publishing Fund of Karlsruhe Institute of Technology.
Keywords: Research Subject Categories::NATURAL SCIENCES:Physics; Austenitic steel; Mechanical alloying; Oxide dispersion strengthened steel; Process control agent; Transmission electron microscopy; X-ray absorption spectroscopy